2013
DOI: 10.7314/apjcp.2013.14.1.367
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Gastric Epithelial AGS Cells Infected with Epstein-Barr Virus

Abstract: Effects of the Epstein-Barr virus (EBV) on cellular protein expression are essential for viral pathogenesis. To characterize the cellular response to EBV infection, differential proteomes of gastric epithelial AGS cellswere analyzed with two-dimensional gel electrophoresis (2-DE) followed by matrix-assisted laser desorption/ionizationtime of flight (MALDI-TOF) and liquid chromatography electrospray/ionization ion trap (LC-ESI-IT) mass spectrometry identification. Mass spectrometry identified 9 altered cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…GDF11 plays intensive roles in development, aging and disease (McPherron et al , ; Nakashima et al , ; Yokoe et al , ; Augusciak‐Duma & Sieron, ; Ding et al , ; Loffredo et al , ; Kaiser, ; Katsimpardi et al , ; Alvarez et al , ; Jamaiyar et al , ; Zhang et al , ), and was recently identified as a regulator of erythropoiesis, which maintains the survival of erythroid progenitors but inhibits further differentiation (Carrancio et al , ; Suragani et al , ). The beneficial effects of GDF11 inhibition were previously reported to be involved in activin receptor ligand traps on terminal erythropoietic differentiation in the mouse models of myelodysplastic syndrome and β‐thalassaemia (Dussiot et al , ; Suragani et al , ; Suragani et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…GDF11 plays intensive roles in development, aging and disease (McPherron et al , ; Nakashima et al , ; Yokoe et al , ; Augusciak‐Duma & Sieron, ; Ding et al , ; Loffredo et al , ; Kaiser, ; Katsimpardi et al , ; Alvarez et al , ; Jamaiyar et al , ; Zhang et al , ), and was recently identified as a regulator of erythropoiesis, which maintains the survival of erythroid progenitors but inhibits further differentiation (Carrancio et al , ; Suragani et al , ). The beneficial effects of GDF11 inhibition were previously reported to be involved in activin receptor ligand traps on terminal erythropoietic differentiation in the mouse models of myelodysplastic syndrome and β‐thalassaemia (Dussiot et al , ; Suragani et al , ; Suragani et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in proteomic approaches have prompted several recent studies of different aspects of the EBV life cycle. Some of these studies have evaluated changes in expression levels of cellular proteins as well as interactions of the latency protein EBNA1 with the cellular proteins nucleophosmin and hnRNP in EBV-infected epithelial cell lines (32,33). Other studies have identified modifications of cellular proteins in response to EBV infection of B cells (34) and identified cellular proteins that are incorporated into herpesvirus virions (35).…”
Section: Discussionmentioning
confidence: 99%
“…Epstein-Barr virus (EBV) is a member of the gamma herpesviruses and was the first confirmed human tumor virus (Ding et al, 2013;Lu et al, 2017). EBV ubiquitously infects more than 90% of the global population and is closely associated with the development of several malignancies, including Burkitt's lymphoma and nasopharyngeal carcinoma (NPC) (Shair et al, 2008;Yu et al, 2012;Young, 2014;Young and Dawson, 2014;Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%